The effect of plasticizer content and disaccharide type on the mechanical, barrier and physical properties of bovine gelatin-based films - Guerrero, Pedro; Zainal Abedin, Nur Hanani; De La Caba, Koro (School of Engineering, Taylor’s University College, 2014)
Gelatins are regarded as alternative raw materials to prepare films for food packaging. However, the improvement of their mechanical and water barrier properties is necessary in order to obtain useful materials in service conditions. To improve these functional properties, two strategies have been carried out in this work. First, glycerol was added as plasticizer to increase the flexibility of the films. Second, lactose or sucrose was added to react with gelatin and increase water resistance of gelatin-based films. Commercial gelatin, glycerol and lactose or sucrose were employed in this work and processing of the films was carried out by solution casting. All gelatin films obtained were transparent and flexible. Moreover, the hydrophobic character of the films was increased and the film solubility was decreased by the addition of glycerol and disaccharides. As was observed via FTIR, the changes were due to the interactions between gelatin and glycerol and Maillard reaction between gelatin and disaccharides.